Cambridge lower secondary English workbook 8 - Elsdon, Graham (United kingdom : Cambridge university press, 2021)
The Cambridge Lower Secondary English Workbook 8 is designed to complement the Learner's Book 8, providing students with additional practice and reinforcement of their language skills. It focuses on grammar, vocabulary, reading comprehension, writing, and speaking, offering a variety of exercises that help solidify students' understanding of English and improve their proficiency.
Keywords: English : Workbook